2000
DOI: 10.1046/j.1462-5822.2000.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia-dependent biosynthesis of a heparan sulphate-like compound in eukaryotic cells

Abstract: SummaryOne hypothesis for the mechanism of chlamydial interaction with its eukaryotic host cell invokes a trimolecular mechanism, whereby a Chlamydia-derived glycosaminoglycan bridges a chlamydial acceptor molecule and a host receptor enabling attachment and invasion. We show that a heparan sulphate-speci®c monoclonal antibody speci®cally binds a glycosaminoglycan localized to the surface of the chlamydial organism and effectively neutralizes infectivity of both C. trachomatis and C. pneumoniae. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…Chlamydiae are capable of binding heparan sulfate, and, consequently, the presence of heparan sulfate on the surfaces of host cells might be expected to affect adherence (2,5,12,26). This interaction is further complicated by data from several laboratories showing that chlamydial EB display heparan sulfate or a functionally analogous compound on their surfaces prior to infection (2,4,8,18,25,26). Moreover, it has recently been shown that fibronectin is also sequestered to the surfaces of EB as a natural outcome of in vitro infection and that fibronectin binding to EB is mediated by heparan sulfate lyase-sensitive components (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydiae are capable of binding heparan sulfate, and, consequently, the presence of heparan sulfate on the surfaces of host cells might be expected to affect adherence (2,5,12,26). This interaction is further complicated by data from several laboratories showing that chlamydial EB display heparan sulfate or a functionally analogous compound on their surfaces prior to infection (2,4,8,18,25,26). Moreover, it has recently been shown that fibronectin is also sequestered to the surfaces of EB as a natural outcome of in vitro infection and that fibronectin binding to EB is mediated by heparan sulfate lyase-sensitive components (13).…”
Section: Discussionmentioning
confidence: 99%
“…twofold) in susceptibility to chlamydial infection were observed for heparan sulfate-deficient CHO-761 cells (26). Larger reductions were observed for CHO-677 and CHO-745 cells (four-to eightfold); nevertheless, like the parental cell line CHO-K1, each cell line can readily be Ͼ90% infected using static inoculation (18). It was concluded that the reductions in infectivity for these CHO cell mutants were less than would be expected with the loss of a host cell surface molecule essential for the infection process.…”
mentioning
confidence: 97%
“…The most common such agent is Chlamydia pneumoniae [154,155]. Chlamydia pneumoniae can only grow and survive inside a host cell, where it accumulates in vacuolae and produces a glycosaminoglycan which bears an extremely strong resemblance to heparan sulfate [156]. We hypothesize that C. pneumoniae may be playing a protective role in providing heparan sulfate to the vasculature.…”
Section: Heparan Sulfate Proteoglycans and Glucose Metabolismmentioning
confidence: 98%
“…Chlamydia is especially significant for our arguments, as it has been demonstrated in in vitro studies that Chlamydia is capable of producing a type of polysaccharide that is almost indistinguishable from heparan sulfate [176]. High concentrations of this polysaccharide were detected specifically in intracellular vacuoles harboring Chlamydia, in three strains of eukaryotic cells that were impaired in different ways in their ability to produce heparan sulfate.…”
Section: Anergy and Serotonin Impairmentmentioning
confidence: 95%